Opportunity Analysis of Construction Retail Business Using Approach Value Proposition - Martin Senjaya Putra Utama; Kristina Sisilia (Jurnal Sekretaris dan Administrasi Bisnis, 2018)
The aims of this research are to find out the proposition value for Sumber Rizqie Abadi’s (SRA) customers, to find out the customer’s perceptions and expectations, to find out the result of value adjustment with customer’s perceptions, and to find out the value proposition’s role for SRA. This research is descriptive with qualitative approach. The techniques of collecting data are interview, observation, and documentation. This study implements design canvas value proposition taken from Alexander Osterwalder and Yves Pigneur to determine value proposition. This has the purpose to show the adjustment between value map from SRA and customer profile from SRA’s segment. Therefore, the result of the adjustment is able to reduce the gap from SRA’s value and customer perceptions value map as SRA’s area have three parts namely products and services, gain creator, and pain relievers. Meanwhile, the customer profile as the costumer’s area also has three parts, specifically jobs, gains, and pains. The results indicated that there are some gaps between the customer’s perceptions and SRA’s value. The gaps among others, the product quality same as the specification, the completeness of goods, supplying the industry needs, saving the money for building a dwelling, delivering the products to customers, and the products just available in SRA.